Modified Luneburg Lens Based on Metamaterials. (18th May 2015) - Chen, Haibing; Cheng, Qiang; Huang, Aihua; Dai, Junyan; Lu, Huiying; Zhao, Jie; Ma, Huifeng; Jiang, Weixiang; Cui, Tiejun
Abstract : We present the design, fabrication, and experimental characterization of a modified two-dimensional Luneburg lens based on bulk metamaterials. The lens is composed by a number of concentric layers. By varying the geometric dimensions of unit cells in each layer, the gradient refractive index profile required for the modified Luneburg lens can be achieved. The cylindrical waves generated from a point source at the focus point of the lens could be transformed into plane waves as desired in the microwave frequency. The proposed modified Luneburg lens can realize wide-angle beam scanning when the source moves along the circumferential direction inside the lens. Numerical and experimental results validate the performance of the modified Luneberg lens.